Analysis in mods: Evaluating game-changing mods - Oliveira, Pedro Arruda de; Silva, Bruno Correia da; Rocha, André (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2025)
Introduction: The use of game modifications (mods) has increasingly become an alternative for diversifying the core gameplay experience, enabling the incorporation of new complex narratives and expansions with extensive symbol usage. Objective: This study aims to analyze three mods of the game Doom, focusing on the practice of "game-changing mods" or "genre-bending mods". The goal is to examine the transformations these mods bring to the original design and the presence of narrative through environmental storytelling. Methodology or Steps: The analysis was conducted using semiotic methods, evaluating visual representations, abstract elements usage, player feedback, and incorporation of narrative through environment in the analyzed mods. Results: The three analyzed mods demonstrated significant modifications from the original Doom design. Transformations included changes in visual representations, innovative use of abstract elements, and impactful player feedback mechanisms.Additionally, an embedded narrative through environmental storytelling was observed in these mods. The results illustrate that "game-changing mods" and "genre-bending mods" not only significantly alter the core gameplay experience but also introduce new narrative elements through environmental means. These mods expand players’ interaction capabilities within the game, offering a fresh perspective on the boundaries of creativity in digital game design.